On the Measurement of Judicial Ideology. (2nd April 2016) - Johnston, Christopher D.; Mak, Maxwell; Sidman, Andrew H.
ABSTRACT: Researchers cannot assess the importance of ideology to judicial behavior without good measures of ideology, and great effort has been spent developing measures that are valid and precise. A few of these have become commonly used in studies of judicial behavior. An emphasis has naturally been placed on developing continuous measures of ideology, like those that exist for other institutions. There are, however, concerns with using continuous measures because they are built on two assumptions that may be untenable when examining judicial decision-making: that the level of precision assumed by these measures is capturing true ideological distinctions between judges, and that the effects of ideology as measures are uniform across levels. We examine these assumptions using different specifications of ideology finding that categorical measures are more valid and better depict the impact of ideology on judicial decision-making at the U.S. Courts of Appeals, but not the Supreme Court.